Legal Regulation of Online Food in Indonesia: Challenges for Public Health and Its Comparison with Malaysia - Laot Kian, Antonius Maria; Ginting, Febriyanti Angelia; Setyowati, Putri Ratna (Riwayat: Educational Journal of History and Humanities, 2025)
This study examines the phenomenon of the rapid growth of online food services in Indonesia through platforms such as GoFood, GrabFood, and ShopeeFood. The popularity of this service is driven by the ease of ordering food, where the assessment of food preferences is often based on the reviews of other users. However, there are concerns that these reviews could be affected by bot ratings or automated systems, which can give a false positive impression. High ratings often make a food product sell better, even though it may contain health risks for consumers. The relationship between online food services and Indonesia's public health is a major concern, given the high consumption of potentially unhealthy foods. The biggest challenge is how to regulate these services in relation to public health. The absence of a law that specifically regulates online food services is a major regulatory issue. The current law only regulates the Law on Information and Electronic Transactions, which was last amended by Law of the Republic of Indonesia Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions. Law of the Republic of Indonesia Number 8 of 1999 concerning Consumer Protection and Law of the Republic of Indonesia Number 18 of 2012 concerning Food, do not also regulate in detail. Comparison with Malaysia, consumers are protected by the Food Act 1983, which requires restaurants and online food platforms to ensure food safety standards, which is more details than Indonesian regulation.